Maternal antenatal vitamin D supplementation and offspring risk of atopic eczema in the first 4 years of life: evidence from a randomized controlled trial. (1st November 2022) - El‐Heis, Sarah; D'Angelo, Stefania; Curtis, Elizabeth M.; Healy, Eugene; Moon, Rebecca J.; Crozier, Sarah R.; Inskip, Hazel; Cooper, Cyrus; Harvey, Nicholas C.; Godfrey, Keith M.; ,
Summary: Background: Evidence linking prenatal maternal vitamin D supplementation with the offspring's risk of atopic eczema is inconsistent, with most data coming from observational studies. Objectives: To examine the influence of maternal cholecalciferol supplementation during pregnancy on the risk of atopic eczema in the offspring at ages 12, 24 and 48 months. Methods: Within the UK Maternal Vitamin D Osteoporosis Study (MAVIDOS) double‐blind, randomized placebo‐controlled trial, we examined the relationship of maternal vitamin D supplementation during pregnancy with offspring atopic eczema at ages 12, 24 and 48 months. In MAVIDOS, pregnant women were allocated to either cholecalciferol 1000 IU per day or matched placebo, taken from around 14 weeks' gestation until delivery, with the primary outcome of neonatal whole‐body bone mineral content. The prevalence of atopic eczema in the offspring was ascertained at ages 12 (n = 635), 24 (n = 610) and 48 (n = 449) months, based on the UK Working Party criteria for the definition of atopic dermatitis. The trial was registered with ISRCTN (82927713) and EudraCT (2007‐001716‐23). Results: The characteristics of mothers and offspring were similar between the intervention and placebo groups, apart from longer breastfeeding duration in the intervention group. Adjusting for breastfeeding duration, offspring of mothers who received cholecalciferol 1000 IU daily had a lower odds ratio (OR) of atopic eczema at age 12 months [OR 0·55, 95% confidence interval (CI) 0·32–0·97, P = 0·04]; this effect weakened and was not statistically significant at ages 24 months (OR 0·76, 95% CI 0·47–1·23) or 48 months (OR 0·75, 95% CI 0·37–1·52). The statistical interaction of intervention and breastfeeding duration in relation to eczema at age 12 months was not significant (P = 0·41), but stratification showed reduced infantile eczema risk in the intervention group for infants breastfed for ≥ 1 month (OR 0·48, 95% CI 0·24–0·94, P = 0·03) but not in those breastfed for < 1 month (OR 0·80, 95% CI 0·29–2·17, P = 0·66). Conclusions: Our data provide the first randomized controlled trial evidence of a protective effect of antenatal cholecalciferol supplementation on the risk of infantile atopic eczema, with the effect potentially being via increased breast milk cholecalciferol levels. The findings support a developmental influence on atopic eczema, and point to a potentially modifiable perinatal influence on atopic eczema. What is already known about this topic?   There are currently no antenatal interventions proven to reduce the incidence of infantile atopic eczema in the general population. However, observational studies have led to speculation that antenatal vitamin D supplementation may be beneficial. Abstract: Our data, from the MAVIDOS double‐blind, randomized controlled trial, demonstrated a reduction in the risk of atopic eczema in infancy following maternal cholecalciferol supplementation during pregnancy; findings were weaker at ages 24 and 48 months. The protective effect of maternal cholecalciferol supplementation on infantile eczema was only significant in offspring breastfed for more than one month, but interaction terms between supplementation during pregnancy and breastfeeding duration were not statistically significant. The findings support a developmental influence on infantile atopic eczema and point to gestational cholecalciferol supplementation as a preventive strategy to reduce the burden of atopic eczema during infancy. Linked Comment:  D. Orchard. Br J Dermatol 2022; 187:630–631 .